HUBUNGAN DIFERENSIASI PRODUK TERHADAP PERILAKU KONSUMEN DI UD. AINE TELUKDALAM - Rosa Delima Dakhi (Universitas Nias Raya, 2026)
The aim of this research is to determine the relationship between product differentiation and consumer behavior at UD. Aine Telukdalam. The type of research used is causal, quantitative. The data source is consumers, with the population and sample in this study being 37 respondents. The data collection technique is a research instrument or questionnaire. The data analysis method used is simple correlation analysis. The results of this research show that the correlation value is 0.668. This research can be concluded that there is a relationship between product differentiation and consumer behavior at UD. Aine Telukdalam. The suggestions for this research are (1) To increase sales volume, it is best for UD. Aine needs to provide promotions on each product. (2) To make consumers comfortable when making purchases, it is best to organize each type of product so that the shop atmosphere looks neat.